2005
DOI: 10.1016/j.femsle.2005.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a chlorpyrifos and 3,5,6-trichloro-2-pyridinol degrading bacterium

Abstract: A bacterium, isolated from contaminated soils around a chemical factory and named strain DSP3 was capable of biodegrading both chlorpyrifos and 3,5,6-trichloro-2-pyridinol. Based on the results of phenotypic features, phylogenetic similarity of 16S rRNA gene sequences, DNA G+C content, and DNA homology between strain DSP3 and reference strains, strain DSP3 was identified as Alcaligenes faecalis. Chlorpyrifos was utilized as the sole source of carbon and phosphorus by strain DSP3. We examined the role of strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
99
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(107 citation statements)
references
References 36 publications
5
99
0
3
Order By: Relevance
“…The successful removal of OP insecticides in soil through the addition of bacteria had been previously reported, but (Singh et al, 2004;Yang et al, 2005Yang et al, , 2006Li et al, 2007;Anwar et al, 2009). The degradation of high concentration of different pesticides by isolated microorganisms has been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The successful removal of OP insecticides in soil through the addition of bacteria had been previously reported, but (Singh et al, 2004;Yang et al, 2005Yang et al, , 2006Li et al, 2007;Anwar et al, 2009). The degradation of high concentration of different pesticides by isolated microorganisms has been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Anwar et al (2009) also reported the CP-degrading strains Bacillus pumilus C2A1. In addition, Yang et al (2005) isolated Alcaligenes faecalis DSP3, which could degrade not only CP but also PT and DZ. Cho et al (2009) also reported that four kimchi-lactic acid bacteria could degrade coumaphos, DZ, PT, MPT, and CP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations